2010 drug interaction facts : the authority on drug interactions - Tatro, David S. (Saint Louis, Mo. : Facts & Comparisons ; London : Lippincott Williams & Wilkins Europe [distributor], 2009)
Provides health professionals with an interaction screening tool, with over 18,000 monographs. This book offers information on the onset, severity, and documentation of clinically significant interactions, including a review of their effects, mechanism, and management
Includes bibliographical references and index.
Keywords: Drug interactions -- Handbooks, manuals, etc